Composite Materials in the Construction of Transport Means - Miloš, Katica; Miloš, Ivan; Čurepić, Danko (Promet - Traffic&Transportation, 2004)
The saving of energy by reducing the mass of the materialrepresents one of the basic requirements in the development ofthe transport technology. High potential in this direction hasbeen recognised in the relatively new group of materials knownas the composites. Their application is expected to achieve greatreduction in the mass of the transport means, especially theroad and railway vehicles. This paper attempts to present informationabout the composites, their status as well as the possibilitiesof their mass implementation.